Diffusion of heavy quarks in the early stage of high-energy nuclear collisions - Pooja; Das Santosh Kumar; Greco Vincenzo; Ruggieri Marco (EPJ Web of Conferences)
We study the diffusion of heavy quarks in the early stage of highenergy nuclear collisions. The pre-equilibrium stage of relativistic heavy-ion collisions, commonly known as Glasma, evolves according to the classical Yang-Mills equations. Heavy quarks are coupled to the evolving Glasma fields via relativistic kinetic theory. We compute the momentum broadening, σp as well as the angular momentum fluctuations of heavy quarks in the early stage, which turn out to be anisotropic due to the anisotropy of the background gluon fields. We observe that σp ∝ t2 at very initial times. This non-Markovian diffusion of heavy quarks in the early stages is explained by the memory effect present in the gluon fields.